Guided Worksheet Formal Definition of Limit: An Instrument Development Process - Rina Oktaviyanthi; Ria Noviana Agus (STAI Hubbulwathan Duri, 2021)
This study aims to develop a guided worksheet to fulfil the needs of students to understand the formal concept of Limit. This was carried out using a developmental study that focuses on content analysis and expert review through substantial analysis, structural design, prototype development and evaluation. The research sample was 95 first-year students, especially those in engineering and science majors who enrolled in Calculus. The data process of instrument development, the data of expert validation, and the data of limited trial were produced in this research. To assess all the research data applied the Q-Cochran and the Cronbach Alpha statistical test. The results are a guided worksheet for limit evaluation in visual form with schematic design and scaffolding or framework type. Expert testing and limited testing showed Asymp.Sig. = 0,088 0,05 and rcoefficient = 0,382 rcritical = 0,2017. It indicates that the items composing this guided worksheet are valid and reliable therefore, they can be used to solve student difficulties related to the formal rules of Limit.